Possible deletion of a developmentally regulated heavy-chain variable region gene in autoimmune diseases. - Yang, P M (1990)
Several autoantibody-associated variable region (V) genes are preferentially expressed during early ontogenic development, suggesting strongly that they are of developmental and physiological importance. As such, it is possible that polymorphisms in one or more of these genes may alter susceptibility to autoimmune disease. We have searched extensively for a probe related to a developmentally regulated V gene that has the power to differentiate among highly homologous V genes in human populations. Using such a probe (i.e., Humhv3005/P1) related to both anti-DNA and anti-IgG autoantibodies, we studied restriction fragment length polymorphisms in patients with rheumatoid arthritis and systemic lupus erythematosus and found an apparent heavy-chain V (VH) gene deletion that was nearly restricted to the autoimmune patients. These data suggest that deletions of physiologically important VH genes may increase the risk of autoimmunity through indirect effects on the development and homeostasis of the B-cell repertoire.